T-DNA of a crown gall tumor is organized in nucleosomes - Schäfer, W. (1984)
Nucleosomes were isolated from chromatin of suspension cultured cells of Nicotiana tabacum var. White Burley, which were either habituated or transformed by Agrobacterium tumefaciens, strain T37. Chromatin repeat length in both types of tissue was identical and can be estimated to be 195 ± 10 bp. Using Southern transfer of nucleosomal DNA and hybridization with cloned nick-translated HindIII fragments of pTi C58 we show that the T-DNA originating from the Ti-plasmid of A. tumefaciens is organized in nucleosomes within the chromatin of crown gall tumor cells.